Utilization of Artificial Intelligence (AI) in Learning: In-House Training for Teachers at SMAN 3 Kota Bengkulu, Indonesia - Eko Risdianto; Tri Basuki Kurniawan; Yupika Maryansyah; Agus Riyanto (Asosiasi Profesi Multimedia Indonesia, 2025)
The In-House Training (IHT) for SMA 3 Bengkulu City teachers aims to improve teachers' skills in utilizing Artificial Intelligence (AI) technology in the learning process. Along with the rapid development of technology, especially in education, the application of AI is expected to enrich the teaching and learning experience and support learning effectiveness. This activity includes the introduction of AI for education, the usage of various AI tools in developing teaching modules, presentations, mind maps, learning videos, and assessments. This training involved more than 80 teachers from various subjects and was tutored by three instructors from Universitas Bengkulu, Universitas Muhammadiyah Bengkulu, and STIKES Bakti Husada Bengkulu. In addition, an evaluation of the quality of training was carried out through a questionnaire that measured respondents’ responses on materials, facilities, delivery, and application of AI in teaching. The results of the data analysis showed that the majority of participants were satisfied with the material provided, with the highest average score on an aspect of material attraction, namely 4.58. However, some areas that need improvement include the provided facilities and time for practice activities. The implication of these findings is the importance of improving training facilities and time so that teachers are better prepared to implement AI technology in learning. This training program has made a significant contribution in preparing teachers to deal with educational challenges in today's digital era.